EFEKTIFITAS SISTEM PEMBELAJARAN ONLINE DALAM MENCAPAI TUJUAN PEMBELAJARAN (Studi Pada SMP Negeri 1 Kasembon) - Arie Wahyu Ramadhani; Hadiwiyono Hadiwiyono (JOURNAL AKSES STIA MALANG, 2021)
The existence of a pandemic has an impact on all fields, including learning. Online learning oronline learning is learning that uses the internet network with accessibility, connectivity, flexibility, andthe ability to produce various types of learning interactions. Online learning is considered to be a veryeffective solution to prevent the spread of Covid. This study aims to determine and analyze theeffectiveness of the online learning system in learning objectives at SMP Negeri 1 Kasembon, MaranRegency. The type of survey used is interactive data.The results of the study prove that online learning at SMP Negeri 1 Kasembon, Maran Regency isvery effective. The learning implementation plan (RPP) used is a single learning implementation planin accordance with students' understanding of the material provided by the teacher to studentsSupporting elements of online or bold learning, namely the school provides Wi-Fi -Fi for schoolteachers as a means to help students with Keywords : Educational Services, Effectiveness, Online System Learning, Learning Objectives